Studi pendahuluan: Korelasi Aktivitas Antikolesterol dengan Aktivitas Antioksidan Ekstrak Etanol Daun Salam (Syzygium polyanthum) - Wijaya, Sumi; Yonas, Stefani Maureen Kasih; Hartanti, Lanny; Setiawan, Henry K.; Soegianto, Lisa (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2018)
Bay leaf leaves (Syzygium polyanthum) are known to have anti-cholesterol activity, with the mechanism inhibited HMG-CoA Reductase enzyme. The purpose of this study was to determine the correlation between anticholesterol activity of bay leaf ethanol extract obtained by percolation method and its antioxidant activity. The parameter used to measure anticolesterol activity is the IC50 value. Antioxidant activity was evaluated by DPPH and Frap methods. The results showed that the ethanolic extract of bay leaves had an IC50 value of 49.50 ± 0.70 ppm. Ethanol extract of bay leaf showed antioxidant activity with IC50 value of 888.0835 ppm and equality of values with 1 mM FeSO4 of 295 ppm. Based on the results of the analysis, the anticholesterol activity of Bay leaf ethanol extract in inhibiting the HMG-CoA Reductase enzyme did not have a linear correlation with its antioxidant activity.